EFL Students' Perception on the Teacher's Role in Zoom-Mediated Speaking Class - Putri, Nurfadilah (IAIN KENDARI, 2024)
This study aims to investigate student’s perception toward teacher’s roles in teaching speaking through zoom. The participants of this study consisted of 20 students including 4 male students and 16 female students from Speaking class of English education major in IAIN Kendari academic year 2021 that were selected based on their ability with their lecturer’s advice. The qualitative data were used in analyzing the data that consisted of two instruments which are questionnaire and interview. The result of this study revealed that the role of teacher's that apply in speaking class through zoom application can help students to improve their speaking ability. Although through zoom application, it can also help their speaking ability; however students still choose to learn through face to face. It means, students feel learn in classroom more effective than through zoom application.